Pengaruh Motivasi Kerja terhadap Produktivitas Kerja Karyawan PT Astra Credit Companies Cabang Fatmawati - Astri Febriyanti; Rendika Vhalery; Deta Muliyani (Neolectura, 2022)
The purpose of the study was to determine the effect of work motivation on work productivity of employees of PT. Astra Credit Companies Fatmawati Branch. This research is an associative research with quantitative type. The population and research sample are employees of PT. Astra Credit Companies Fatmawati Branch with 128 employees. Methods of data collection using a questionnaire. The data analysis technique used simple linear regression analysis and hypothesis testing. The results showed that the simple linear regression value was Y = 24.55 + 0.58X. The results of the correlation calculation above can be concluded that the correlation coefficient rxy = 0.988, meaning that the correlation between work motivation (X) and work productivity (Y) is in the very high category. The value of the coefficient of determination (KD) is 97.6%. This means that work motivation has an effect on work productivity of 97.6% while the remaining 2.4% is the influence of other variables not examined. The results of the hypothesis test show that H0 is rejected and Ha is accepted, which means that there is an influence of work motivation on the work productivity of PT. Astra Credit Companies Fatmawati Branch positively and significantly